2015
DOI: 10.1007/s40860-015-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Designing for user confidence in intelligent environments

Abstract: Intelligent environments aim at supporting and assisting users in their daily activities. Their reliability, i.e., the capability of correctly accomplishing the intended tasks and of limiting or avoiding damage in case of malfunctions, is essential as for any user-facing technology. One aspect of reliability, often neglected, is guaranteeing the consistency between system operation and user expectations, so that users may build confidence over the correct behavior of the system and its reaction to their action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Pennings et al [20] reported that success of an intelligent environment is mainly determined by the extent to which it is adopted by users. Corno et al [7] carried an extensive literature review on the involvement of users in the research, design, development, and validation of intelligent environments over the last 15 years. They also emphasized that IEs should be built with the users in mind and made a strong case for user-appreciated systems.…”
Section: U-c Iedpmentioning
confidence: 99%
“…Pennings et al [20] reported that success of an intelligent environment is mainly determined by the extent to which it is adopted by users. Corno et al [7] carried an extensive literature review on the involvement of users in the research, design, development, and validation of intelligent environments over the last 15 years. They also emphasized that IEs should be built with the users in mind and made a strong case for user-appreciated systems.…”
Section: U-c Iedpmentioning
confidence: 99%
“…A growing number of studies have emphasized the importance of participatory and user-centered design since decisions on solutions' design, made independently of users can reduce user acceptance ( 36 – 38 ). Yet, a technocentric approach still seems to persist in AAL developments, resulting in solutions that are high-tech but have low impact for end users ( 39 41 ). Participatory design and collaboration among the different stakeholders and end users need to be reinforced in projects and policies when developing smart living environments.…”
Section: Discussionmentioning
confidence: 99%
“…Pennings et al (2010) reported that success of an Intelligent Environment is mainly determined by the extent to which it is adopted by users. Corno et al (2015) carried out an extensive literature review on the involvement of users in the research, design, development and validation of intelligent environments over the last 15 years. They also emphasised that IEs should be built with the users in mind and made a strong case for user-appreciated systems.…”
Section: U-c Iedpmentioning
confidence: 99%